Analysis of Hate Speech in the Comments Column of the Instagram Account @ahmadsahroni88: A Pragmatic Study - Sahrina Putri Utami; Eko Muharudin; Laili Nurlina; Isnaeni Praptanti (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe and classify the forms of hate speech found in the comment section of the Instagram account @ahmadsahroni88 during the period of September to October 2025 based on illocutionary speech acts within a pragmatic framework. This research employs a descriptive qualitative method. The object of the study is hate speech containing elements of insult, defamation, blasphemy, and provocation. Primary data sources were obtained from the comment columns of posts on the Instagram account @ahmadsahroni88, while secondary data were derived from books, journals, and relevant academic articles. The population includes all comments posted during the specified period, with samples taken using random sampling techniques based on hate speech criteria. The research instrument was the researcher as a human instrument, supported by a documentation instrument table. Data collection techniques involved documentation and note-taking methods. The validity of the data was tested using theoretical triangulation by comparing the data with Searle’s theory of illocutionary speech acts. The data analysis tool followed the Miles, Huberman, and Saldana model through three stages: data reduction, data display, and conclusion drawing and verification. The results of the study indicate that the forms of hate speech identified include (1) representative illocutionary speech acts containing insults, defamation, and blasphemy; (2) directive illocutionary speech acts containing insults, blasphemy, and provocation; and (3) expressive illocutionary speech acts containing insults, defamation, and blasphemy.